Bioaccumulation and Risk Assessment of Potentially Toxic Elements in Soil-Rice System in Karst Area, Southwest China - Zhang, Chunlai; Zou, Xia; Yang, Hui; Liang, Jianhong; Zhu, Tongbin (Frontiers in Environmental Science, 2022)
The accumulation of potentially toxic elements (PTE) in soil–rice system poses a serious issue of concern in agricultural soils, particularly in the polluted or high PTE geological background regions, such as karst areas. The source identification, bioaccumulation factors of PTE and its health risk were investigated by correlation analysis, principal components Analysis and single/comprehensive assessments in soil-rice system in Mashan County, Guangxi province. The results showed that the mean contents of PTE in rice rhizosphere soil samples were higher than Guangxi surface soil, but lower than Mashan background. 84.21% of the samples have Cd content exceeding the soil environmental quality -- risk control standard for soil contamination of agricultural land in China (GB 15618-2018) risk screening value. The nemerow comprehensive pollution index indicated that 21.05% and 26.32% of the soil samples were moderately and heavily polluted. The contents of pH-related exchangeable Ca, exchangeable Mg, and redox-related available Fe and available Mn in soil affected the bioaccumulation of PTE in rice. In all the rice samples, 55.26% of Cd and 31.58% of Pb exceed the maximum allowable value of contaminants in rice recommended by the national food safety standard for maximum levels of contaminants in foods in China (GB 2762-2017). The average targeted hazard quotient values (THQ) of PTE decreased in an order of As >Cd>Cr >Cu >Zn >Pb >Hg, and the degree of health risk it posed to the population was Children>Female >Male. The hazard index (HI) of all samples was greater than 1 due to all THQAs and the THQCd of more than half samples were above 1, which implied that the residents were exposed to non-carcinogenic risk by rice ingestion. Therefore, the PTE in the karst area with a high geological background can be absorbed and migrated by crops, leading to a greater health risk to human, which should be paid attention to in future research and agricultural management.